Initial memory consolidation and the synaptic tagging and capture hypothesis. (25th July 2020) - Okuda, Kosuke; Højgaard, Kristoffer; Privitera, Lucia; Bayraktar, Gülberk; Takeuchi, Tomonori
Abstract: Everyday memories are retained automatically in the hippocampus and then decay very rapidly. Memory retention can be boosted when novel experiences occur shortly before or shortly after the time of memory encoding via a memory stabilization process called "initial memory consolidation." The dopamine release and new protein synthesis in the hippocampus during a novel experience are crucial for this novelty‐induced memory boost. The mechanisms underlying initial memory consolidation are not well‐understood, but the synaptic tagging and capture (STC) hypothesis provides a conceptual basis of synaptic plasticity events occurring during initial memory consolidation. In this review, we provide an overview of the STC hypothesis and its relevance to dopaminergic signalling, in order to explore the cellular and molecular mechanisms underlying initial memory consolidation in the hippocampus. We summarize electrophysiological STC processes based on the evidence from two‐pathway experiments and a behavioural tagging hypothesis, which translates the STC hypothesis into a related behavioural hypothesis. We also discuss the function of two types of molecules, "synaptic tags" and "plasticity‐related proteins, " which have a crucial role in the STC process and initial memory consolidation. We describe candidate molecules for the roles of synaptic tag and plasticity‐related proteins and interpret their candidacy based on evidence from two‐pathway experiments ex vivo, behavioural tagging experiments in vivo and recent cutting‐edge optical imaging experiments. Lastly, we discuss the direction of future studies to advance our understanding of molecular mechanisms underlying the STC process, which are critical for initial memory consolidation in the hippocampus. Abstract : Memory can be boosted when novel experiences occur before or after memory encoding via a memory stabilization process called "initial memory consolidation." This hippocampal dopamine‐dependent novelty‐induced memory boost fits well with the synaptic tagging and capture (STC) hypothesis, which has evidence from two‐pathway electrophysiological experiments. Here, we discuss the crucial roles of "synaptic tags" and "plasticity‐related proteins" in the STC and initial memory consolidation processes.